ANALYSIS OF INTERACTION WITH STAKEHOLDERS OF THE ENTERPRISE: THE PRACTICE OF APPLYING THE STANDARD АА1000SES ON THE EXAMPLE OF THE NATIONAL AEROSOL CLUSTER - Prokhorova, I. S.; Rasskazova, A. Yu (Вестник университета, 2020)
The study of stakeholder relationships in organizations helps to comprehensively assess the external business environment and effectively build communication processes. Consideration of stakeholders in clusters is interesting, since they unite not only the participants of one enterprise, but also organizations of different regions. the communication environment of the cluster is extensive and ambiguous. The subject of the research is the system of relationships that arise between stakeholders and participants of the National Aerosol Cluster in the process of their interaction. The methodological basis is the AA1000SES stakeholder engagement standard and its practical guideline for planning and preparing engagement. The research methodology is based on the analysis of  behavioural motives of cluster stakeholders when interacting with its participants. The analysis determined the key stakeholders of the cluster; mechanisms that ensure an adequate response to the requests of stakeholders;  circumstances that prevent participation of stakeholders in interaction; and identified the benefits of interaction with stakeholders. The study showed that managing interaction with stakeholders can help the National Aerosol Cluster strengthen its position in the production of aerosol products, increase the volume of output and enter new markets.